PRODUCTION EFFECTIVENESS ANALYSIS OF FLOXAD CAPLET AND LAFIDRIL SYRUP : CASE STUDY IN THE PHARMACY DEPARTMENT OF HEALTH DIRECTORATE OF ARMY FORCE, BANDUNG - Andika Purnama Devi; Achmad Fudholi; Samsubar Saleh (Faculty of Pharmacy, Universitas Gadjah Mada)
The Pharmacy Department of Health Directorate of Army Force (Lafi Ditkesad) always continually improved in some aspects, not only focus on product quality yielded, but also on production cost management. Therefore, Lafi Ditkesad should always allocate its production factors suitably and effectively to avoid production factor waste that would harm Lafi Ditkesad. This research was aimed to know work force and machinery production costs towards production output of Floxad caplet and Lafidril syrup medicines in Lafi Ditkesad and to know the effectiveness of input use level in Lafi Ditkesad. Data collection technique was based on a documentation study from Lafi Ditkesad. This was a descriptive quantitative research and an explanatory research supported by a survey method. Analysis of the data was conducted with multiple linear regression analysis modified from a Cobb-Douglas production function model with an SPSS software. A independent variable effect towards a dependent variable was conducted by an F-test and t-test with α = 0.05. The result showed that work force (probability = 0.03) and machinery (probability = 0.00) production factors significantly affected production of Lafidril syrup medicine. Meanwhile, in Floxad caplet production, work force production factor (probability = 0.00) significantly affected the production output, but the machinery production factor (probability = 0.09) did not significantly affect production output. Floxad caplet production effectiveness was better than Lafidril syrup production process. This could be viewed from an effectiveness index from each production function where an effectiveness index of Floxad caplet medicine production was 57641.61, while Lafidril syrup was 4755.23.Keywords: Cobb-Douglas, effectiveness, work force, machine